2008
DOI: 10.1002/bmc.973
|View full text |Cite
|
Sign up to set email alerts
|

Determination of acetylsalicylic acid and its major metabolite, salicylic acid, in human plasma using liquid chromatography–tandem mass spectrometry: application to pharmacokinetic study of Astrix® in Korean healthy volunteers

Abstract: The first liquid chromatography-tandem mass spectrometry (LC/MS/MS) method for determination of acetylsalicylic acid (aspirin, ASA) and one of its major metabolites, salicylic acid (SA), in human plasma using simvastatin as an internal standard has been developed and validated. For ASA analysis, a plasma sample containing potassium fluoride was extracted using a mixture of ethyl acetate and diethyl ether in the presence of 0.5% formic acid. SA, a major metabolite of ASA, was extracted from plasma using protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 22 publications
2
36
0
2
Order By: Relevance
“…3A). Similarly, at concentrations of aspirin and celecoxib achieved in plasma with typical dosages of these drugs (26,27), celecoxib largely prevented aspirin inhibition (Fig. 3B).…”
Section: Resultsmentioning
confidence: 70%
“…3A). Similarly, at concentrations of aspirin and celecoxib achieved in plasma with typical dosages of these drugs (26,27), celecoxib largely prevented aspirin inhibition (Fig. 3B).…”
Section: Resultsmentioning
confidence: 70%
“…However, published pharmacokinetics studies on this aspirin dose have revealed contradictory C max depending on formulation, such as soluble, rapid-release, or chewable 100 mg tablets exhibiting minor differences [22,23,33]; by contrast, the enteric or controlled release tablets showed wide and significant variations [37,38]. Our in vitro results simulated human plasma levels based on 100 mg rapid-acting aspirin formulations (soluble and rapid-release tablets), whose quick action is desirable during the acute onset of symptoms, such as in MI.…”
Section: Discussionmentioning
confidence: 97%
“…The AUC 0-∞ values were 23800 and 21527 ng.h/mL and the t 1/2 was 3.17 and 2.65 h for the test and for the reference formulation, respectively. Bae et al [2] reported values of 3780 ng/mL for C max , 4.45 h for t max , 18200 ng.h/mL for AUC 0-∞ and 2.04 for t 1/2 after a single oral dose administration of an enteric-coated pellets 100 mg acetylsalicylic acid in healthy volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in low-dose it is also used as antithrombotic agent to inhibit cyclooxygenase-dependent platelet aggregation responsible for the formation of thrombi, which may be related to myocardial infarction and stroke [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation